Incidence and risk predictors of acute kidney injury among HIV-positive patients presenting with sepsis in a low resource setting - Kimweri, Davis (BMC Nephrol, 2021)
BACKGROUND: Acute kidney injury (AKI) is a frequently encountered clinical condition in critically ill patients and is associated with increased morbidity and mortality. In our resource-limited setting (RLS), the most common cause of AKI is sepsis and volume depletion. Sepsis alone, accounts for up to 62 % of the AKI cases in HIV-positive patients. OBJECTIVE: The major goal of this study was to determine the incidence and risk predictors of AKI among HIV-infected patients admitted with sepsis at a tertiary hospital in Uganda. METHODS: In a prospective cohort study, we enrolled adult patients presenting with sepsis at Mbarara Regional Referral Hospital (MRRH) in southwestern Uganda between March and July 2020. Sepsis was determined using the qSOFA criteria. Patients presenting with CKD or AKI were excluded. Sociodemographic characteristics, physical examination findings, and baseline laboratory values were recorded in a data collection tool. The serum creatinine and urea were done at admission (0-hour) and at the 48-hour mark to determine the presence of AKI. We performed crude and multivariable binomial regression to establish the factors that predicted developing AKI in the first 48 h of admission. Variables with a p < 0.01 in the adjusted analysis were considered as significant predictors of AKI. RESULTS: Out of 384 patients screened, 73 (19 %) met our inclusion criteria. Their median age was 38 (IQR 29–46) years and 44 (60.3 %) were male. The median CD4 T-cell count was 67 (IQR 35–200) cells, median MUAC was 23 (IQR 21–27) cm and 54 (74.0 %) participants were on a regimen containing Tenofovir Disoproxil Fumarate (TDF). The incidence of AKI in 48 h was 19.2 % and in the adjusted analysis, thrombocytopenia (Platelet count < 150) (adjusted risk ratio 8.21: 95 % CI: 2.0–33.8, p = 0.004) was an independent predictor of AKI. CONCLUSIONS: There is a high incidence of AKI among HIV-positive patients admitted with sepsis in Uganda. Thrombocytopenia at admission may be a significant risk factor for developing AKI. The association of thrombocytopenia in sepsis and AKI needs to be investigated.